2009
DOI: 10.3892/ijo_00000312
|View full text |Cite
|
Sign up to set email alerts
|

The expression and role of serum response factor in papillary carcinoma of the thyroid

Abstract: Abstract. Serum response factor (SRF) is a transcription factor of the MADS box family. SRF is involved in various cellular processes such as expression of immediate early and tissuespecific genes, cell proliferation, differentiation and apoptosis. The expression of SRF in papillary thyroid carcinoma (PTC) and its role have not been investigated, forming the basis for this study. Surgical specimens of 63 conventional PTCs along with 30 follicular adenoma, 30 adenomatous hyperplasia and 9 anaplastic carcinoma s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…MRTF‐A or SRF depletion could reduce the metastasis of both human breast cancer cells and mouse melanoma cells (Medjkane et al, 2009). Overexpression of SRF enhanced the cell motility and invasiveness of hepatocellular carcinoma cells and papillary carcinoma cells (Kim et al, 2009; Kwon et al, 2010). Yin et al also found that SRF was highly expressed in gastric cancer, and disease‐free survival rate and overall survival rate were both significantly lower in patients with high SRF expression (Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…MRTF‐A or SRF depletion could reduce the metastasis of both human breast cancer cells and mouse melanoma cells (Medjkane et al, 2009). Overexpression of SRF enhanced the cell motility and invasiveness of hepatocellular carcinoma cells and papillary carcinoma cells (Kim et al, 2009; Kwon et al, 2010). Yin et al also found that SRF was highly expressed in gastric cancer, and disease‐free survival rate and overall survival rate were both significantly lower in patients with high SRF expression (Yin et al, 2019).…”
Section: Introductionmentioning
confidence: 99%